Spatial Differentiation Of The Economic Structure Of The Russian Regions Of The Arctic Zone - Baklanov, Peter Ya; Moshkov, Anatoly V. (R-Economy, 2015)
The regions situated in the Arctic zone of Russia perform an important function in the implementation of  the  export  potential  of  the  country.  As  one  of  favourable  factors  for  the  development  of  production  in the  Arctic  Zone,  we  have  to  consider  the  richest  natural  and  resource  potential  of  dry  land  and  the  sea. Negative factors limiting the development of the Arctic zone: the harsh natural and climatic conditions and the remoteness of the region from the subjects of the Russian Federation which have a higher level of socio-economic development, low level of economic development (including infrastructure) of these territories, low demographic capacity of the population. The research is aimed at revealing the existing spatial differentiation of the kinds of economic activity in  the  latitudes  of  the  northern  districts  of  the  country. In  order  to  assess  the  differences  in  the  industry structure of the gross added value of all the constituent entities of the Russian Federation whose territories to the Arctic zone, some graphs and map-schemes have been drafted. In addition, the authors also assessed the deviation of the industry breakdown from the average values observed in the Russian Federation as a whole. The analysis of the specifics of the spatial differentiation of the types of economic activity in the economy of the Arctic regions allows to reveal certain trends in the future development of the economic structures.The article is intended for specialists and students interested in the problems of the development of the northern regions of Russia.